2019
DOI: 10.1002/pro.3568
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic identification of spontaneous oxidation intermediates and products of protein sulfhydryl groups

Abstract: In the absence of protective reducing agents, Cys residues in purified proteins can be oxidized spontaneously by oxygen in the air, as frequently observed in protein crystal structures. However, the formation of an O‐bridge via dehydration mechanism between a peroxidized Cys side chain and a primary amine of Lys side chain in proteins has not yet been reported. When an electron density feature was observed for an extra group or an extra atom between side chains of Cys‐245 and Lys‐158 in the crystal structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Wang doubts our claim that the unexpected feature identified as a bridge between the side chains of Lys and Cys in the crystal structure of HPP and some other structures in the PDB is a methylene moiety. In his interpretation, these residues are connected by an O atom.…”
mentioning
confidence: 73%
“…Wang doubts our claim that the unexpected feature identified as a bridge between the side chains of Lys and Cys in the crystal structure of HPP and some other structures in the PDB is a methylene moiety. In his interpretation, these residues are connected by an O atom.…”
mentioning
confidence: 73%
“…4 Wang, however, challenged this conclusion, arguing that the Cys Lys bridge in HPP was via an oxygen atom rather than a methylene group. 5 Applying a method he had previously developed 6 to the experimental data of Ruszkowski and Dauter 4 (PDB code 5EQA), Wang showed that the electron density at the bridge position is consistent with an oxygen atom rather than a methylene group. Wang also argued that covalently-linked cysteine and lysine residues, in general, are joined by an O-bridge.…”
mentioning
confidence: 99%
“…Wang also argued that covalently-linked cysteine and lysine residues, in general, are joined by an O-bridge. 5,7 (Ruszkowski and Dauter 8 have argued that HPP may be something of a special case because the crystals were exposed to formaldehyde which is an agent for crosslinking amines with thiols, but presumably this is not the case for other examples of Cys X Lys linkages. See also Tayri-Wilk et al 9 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A identificação dos resíduos característicos junto com a observação da importância do switch I na interface foi usado para investigar a base estrutural da preferência pela Nos últimos anos tem sido reportada uma nova interação covalente entre os aminoácidos Lys e Cys, via um grupo metilo ou uma molécula de água, em algumas estruturas cristalográficas. [99][100][101] Embora ainda em discussão a natureza química da ligação 101 , decidimos tentar reproduzir os experimentos de formação da ligação entre Lys e Cys em solução, porque em nossos heterodímeros a proximidade entre a Lys111 e Cys111 sugere a possível formação da ligação entre elas (figura 38). Embora a densidade eletrônica e a distância entre a Lys111 e Cys111 não mostre uma interação direta entre os aminoácidos, os 3,9 Å de separação e a flexibilidade de orientação para aminoácidos de lisina sugerem a possível interação entre eles em um ambiente favorável para a formação da ponte Lys-Cys.…”
Section: Resíduos Característicos Envolvidos Em Interações Especificas Do Switch Iunclassified